Surface currents in the western North Atlantic during the Last Glacial Maximum - LeGrande, A. N.; Lynch-Stieglitz, J. (Geochemistry Geophysics Geosystems, 2007)
[1] During the last ice age, the density gradient across the Florida Current was reduced, implying a reduction in the flow of the Gulf Stream through the Florida Straits. Here we investigate the possibility that a significant portion of this wind-driven western boundary flow bypassed the Florida Straits during glacial times due to either changes in bathymetry induced by the sea level drop or changes in wind patterns. Down core records of the oxygen isotope ratios of the planktonic foraminifer Globorotalia truncatulinoides are used to locate the density gradients and thus the locations of upper ocean currents in the western North Atlantic. We find that western boundary flow was largely confined within the Florida Straits during the Last Glacial Maximum as it is today. This finding supports the idea that the reduced density gradient across the Florida Current represents a reduction in the surface branch of the surface to deep meridional overturning circulation in the Atlantic rather than a reduction in the proportion of the wind-driven flow carried by the Florida Current.
131djTimes Cited:2Cited References Count:16